Tocilizumab, an Exploratory Treatment for Severe COVID-19 Patients - Yong Wang; Yongfeng Chen; Xiangdong Zhou (Canadian Journal of Infectious Diseases and Medical Microbiology)
The coronavirus disease 2019 (COVID-19) may cause cytokine storm and respiratory illness such as pneumonia and progressive respiratory failure. Tocilizumab (TCZ), a monoclonal antibody that targets the interleukin-6 (IL-6) receptor, was approved as an alternative treatment for severe COVID-19 patients despite limited real-world clinical data in China. In the present study, we will discuss and evaluate the treatment response of TCZ therapy in patients with COVID-19. The clinical characteristics, treatment, laboratory parameters of IL-6, C-reactive protein (CRP), lymphocyte counts before and after TCZ therapy, and clinical outcomes in the 13 patients with COVID-19 were retrospectively evaluated according to the related medical records. The results showed that 13 patients with COVID-19 were totally included in this study. One of them was moderately ill, 8 were seriously ill, and 4 were critically ill. Eleven patients received TCZ administration once, while the other 2 patients received it twice. The median level of IL-6 before TCZ administration was 27.91 (7.42–210.90) pg/mL. Serum IL-6 level tended to further spike firstly and then gradually decreased after TCZ therapy in 10 patients. A persistent and dramatic increase of IL-6 was observed in 2 patients who were finally dead. The CRP levels of 76.92% (10/13) of the patients were above the normal range before the start of TCZ therapy and gradually declined after the TCZ treatment. No. 1 and No. 10 patients finally died accompanied by the corresponding lymphocyte counts persistently dropping. No. 13 patient became exacerbated possibly due to inducing severe bacterial infection after TCZ treatment, while the other 10 patients showed clinical improvement. In summary, the study revealed that TCZ may have a certain therapeutic effect on severe COVID-19 patients with a risk of the cytokine storm. It is necessary to further evaluate the efficacy and safety of TCZ by rigorous randomized controlled trial in the next step.